DEPICTION OF ISLAM’S COLLAPSES IN ANDALUSIA FROM THE NOVEL SANGKAKALA DI LANGIT ANDALUSIA - Misbahus Surur; Ummi Hasanah; M. Anwar Masadi; Aulia Fadhila Wirmansyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to describe the historical picture of Islam’s collapse during the Andalusian period in novel